2020
DOI: 10.1177/0885328220911585
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of implants with superelastic behaviour for midface reconstruction

Abstract: The proper reconstruction of midfacial defects is an ongoing challenge in the field of reconstructive surgery. One of the principal aims of adequate therapeutic and anatomical reconstruction was to guarantee good functional and aesthetical results. In this context, one of the most challenging areas as regards reconstruction of the facial skeleton is the orbit, which refers to the cavity or socket of the skull in which the eye and its appendages are situated. Today, computerassisted surgery, particularly in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…External stimuli may only activate the actuator system during the surgical intervention. Previous studies conducted by our team [16][17][18] and results from other research groups [19][20][21][22][23][24][25] have shown the potential of shape memory alloys (SMAs), especially nickel-titanium (NiTi), as components for implant applications. NiTi shows sufficient biocompatibility compared to other implant materials, such as Titanium and Titanium alloys, nickel-free stainless steel, or magnesium alloys [26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…External stimuli may only activate the actuator system during the surgical intervention. Previous studies conducted by our team [16][17][18] and results from other research groups [19][20][21][22][23][24][25] have shown the potential of shape memory alloys (SMAs), especially nickel-titanium (NiTi), as components for implant applications. NiTi shows sufficient biocompatibility compared to other implant materials, such as Titanium and Titanium alloys, nickel-free stainless steel, or magnesium alloys [26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%